Disability and the Social Politics of “Natural” Disaster - Belser, Julia Watts (Worldviews, 2015)
The stories we tell about crisis and catastrophe often intensify structural violence, augmenting existing dynamics of racism, sexism, classism, and ableism. Disaster stories often reinforce cultural narratives of suffering womanhood and tragic stories of disability to portray people with disabilities—especially women—as “natural” and “inevitable” victims of a harsh new world. Examining both contemporary rhetoric in the wake of Hurricane Katrina and classical rabbinic Jewish narrative, I argue that tales of communities in crisis commonly depoliticize disaster. By inscribing the disabled body with a narrative of “natural” vulnerabilities and inevitable suffering, conventional disaster discourse obscures the political significance of structural inequalities that render people with disabilities more at risk in disaster. Bringing together disability studies scholarship and Jewish feminist ethics, I challenge the discursive tendency to portray disabled individuals as symbols of suffering—and to focus on the pathos of an individual in distress instead of critiquing social inequality. I advocate a constructive, redemptive storytelling that illuminates and critiques social and political exclusion, that underscores the agency and dignity of people in crisis, that valorizes the disability justice movement’s call for interdependence in community, and that captures the artistry and resiliency of disabled lives.